Analysis of Plasma Farmers' Satisfaction Levels in the Implementation of Partnership with PT. Ciomas Adisatwa in Wonggeduku District, Konawe Regency - Maragi, Muh. Ikhawan Alif Al; Rianse, Ilma Sarimustaqiyma; Yusriadin (International Journal of Technology and Education Research, 2025)
This study aims to determine the level of satisfaction of plasma farmers with the implementation of the partnership program run by PT. Ciomas Adisatwa in Wonggeduku District, Konawe Regency. This partnership is expected to increase farmers' income. The research population consisted of all 8 plasma farmers in Wonggeduku District who collaborated with PT. Ciomas Adisatwa, and data collection was carried out using the census method. Primary data were obtained through interviews using questionnaires, while secondary data were sourced from the Central Statistics Agency (BPS) and relevant government agencies. Data analysis employed descriptive methods for partnership patterns and interval class calculations with a Likert scale for satisfaction levels. The results indicate that the overall satisfaction level of plasma farmers falls into the "satisfied" category, with an average score of 62. The aspects that received the highest satisfaction scores were the quality of feed provided (score 65) and the speed of harvest payment (score 65), both categorized as "very satisfied." Conversely, the aspects with the lowest satisfaction scores were the application of the DOC (Day Old Chick) contract price (score 60), the application of the feed contract price (score 60), and the provision of bonuses (score 60), all of which were categorized as "satisfied." The findings of this study conclude that farmers in Wonggeduku District, Konawe Regency, are generally satisfied with the PT. Ciomas Adisatwa partnership. The findings of this study conclude that farmers in Wonggeduku District, Konawe Regency, are generally satisfied with the PT. Ciomas Adisatwa partnership, although there is room for improvement in contract pricing and bonus provision to optimize farmer satisfaction